IMPROVING READING COMPREHENSION USING STORIES AT MTs MIFTAHUL HUDA SILIR WATES - Muhammad Adib Efendi (LPPM IAI Hasanuddin Pare-Kediri, 2019)
The objective of this research is to improve students’ reading comprehension skills using Stories. The research design used in this study was action research. In this research the reseacher took a test of their improvement in each cycle. Before the reseacher did cycle 1, the reseacher did pre–cycle and found the mean is 64, by percentage of successful is 19% (4 students out of 21) passed the test. In the first cycle the reseacher found the mean of the score of the students reading was 74 by percentage of successful is 57% (12 student out of 21) passed the test. In the second cycle the researcher found the mean of the score of the students reading was 85,7 by percentage of succusful is 86% (18 students out of 21) paased the test. From the observation, the researcher has the criteria of success. they are the average of students’ achievement should be 80, the percentage of successfulness is 80% from the total students, the criteria of minimum passing level (KKM) is 75. The result of the reseach shows that the students improve their ability in reading comprehension by using Stories.